Dispersal and Development of Powdery Mildew Disease Caused by Oidiopsis haplophylli on Ornamental Plants (Nasturtium) Tropaeolum majus L. in Baghdad (Baghdad Science Journal, 2025)
This study wass carried out to investigate the incedence of powdery mildew disease on ornamental plants (Nasturtium) Tropaeolum majus L. caused by Oidiopsis haplophylli in some nurseries of Baghdad area and in fields at college of Agriculture /University of Baghdad. This study was conducted in tow succesive seasons of 2011-2012 (April and May). The survey indicated that the Mildew disease existe in the following nurseries (Al-Adhamiya 97.5% ,Palestine street 93.8%, Zayouna 86.0%, and 100% in two fields at college of Agriculture. It has been found that the disease severity was developed in Agriculture college fields successively from 12-4-2011 to 20-5-2011 and from 12-4-2012 to 20-5-2012 (18.0–98.0 % and 22.7–96.0% )for the two seasons respectively. The records were followed for six times at interval of 7 days.